The Buddha in the attic - Otsuka, Julie, 1962- (New Delhi : Penguin Books, 2012)
Presents the stories of six Japanese mail-order brides whose new lives in early twentieth-century San Francisco are marked by backbreaking migrant work, cultural struggles, children who reject their heritage, and the prospect of wartime internment.
""This is a Borzoi book.""
Keywords: Japanese -- California -- Fiction; Mail order brides -- Fiction; San Francisco (Calif.) -- History -- 20th century -- Fiction